2019
DOI: 10.6004/jnccn.2019.0059
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Non–Small Cell Lung Cancer, Version 1.2020

Abstract: The NCCN Guidelines for Non–Small Cell Lung Cancer (NSCLC) address all aspects of management for NSCLC. These NCCN Guidelines Insights focus on recent updates in immunotherapy. For the 2020 update, all of the systemic therapy regimens have been categorized using a new preference stratification system; certain regimens are now recommended as “preferred interventions,” whereas others are categorized as either “other recommended interventions” or “useful under certain circumstances.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
772
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 810 publications
(811 citation statements)
references
References 33 publications
8
772
0
4
Order By: Relevance
“…The osimertinib treatment line was as follows: second-line (n = 19, 33.9%), third-line (n = 15, 26.8%), and fourth−/later-line (n = 22, 39.3%). The median number of previous regimens was two (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Osimertinib (80 mg/day) was orally administered to all patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The osimertinib treatment line was as follows: second-line (n = 19, 33.9%), third-line (n = 15, 26.8%), and fourth−/later-line (n = 22, 39.3%). The median number of previous regimens was two (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Osimertinib (80 mg/day) was orally administered to all patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The 2018 National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines for Non-Small Cell Lung Cancer (NSCLC) recommend epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) as first-line treatment for unresectable, EGFR mutation-positive, advanced NSCLC. 1 It is known that lung cancer patients with activated EGFR mutations respond to firstor second-generation EGFR-TKIs, such as gefitinib, erlotinib, and afatinib. [2][3][4][5][6][7] However, in many cases, the effects are transient, cause drug resistance, and lead to deterioration in clinical conditions in approximately one year.…”
Section: Introductionmentioning
confidence: 99%
“…The latest report according to world health organization (WHO) showed that lung cancer is the leading cause of morbidity and mortality worldwide malignant tumor. [1][2][3] Unfortunately, despite advances in treatment, the prognosis remains poor. Taking into account all stages at diagnosis, the 5-year survival rate for lung cancer is only 18.1%, while, it is much lower (approximately 4.5%) for those with metastatic disease at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…procedures do not benefit N3 and M1 patients; chemotherapy or radiochemotherapy are the optimal treatments. 2 When a patient is suspected or confirmed with NSCLC, clinical TNM staging mainly based on imaging studies should be conducted to determine if surgery should be considered and what type of surgical procedure (lobectomy or sublobar resection) is preferred. Clinical N stage (cN stage) is established by imaging studies, usually with contrast-enhanced computed tomography (CT) or positron emission (PET)-CT.…”
Section: Introductionmentioning
confidence: 99%